MARKET ORIENTATION AND PRODUCT INNOVATION IMPACT PURCHASING DECISIONS - Rusdiyanto Rusdiyanto; Susetyorini Susetyorini; Umi Elan; Muhammad Afifi Rahman; Nur Farida; Arif Syafi’ur Rochman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to identify and analyze the influence of market orientation and product innovation on purchasing decisions in companies in Gresik. This research was included in quantitative research and the customers who transacted in gresik were the population in the study. The technique of calculating the number of samples uses non-probability sampling. This study sample used customers who ordered the product to contribute to becoming research participants. Data collection is carried out by distributing questionnaires. Some of the data analysis methods used are validity and reliability testing, multiple linear regression analysis, hypothesis testing, and determination coefficient testing. The results of its tests, it has been established that market orientation influences purchasing decisions, while product innovation influences purchasing decisions. The test results show that market orientation and product innovation simultaneously influence product purchasing decisions.